MODULATION OF KEY BIOCHEMICAL MARKERS RELEVANT TO STROKE BY ANTIARIS AFRICANA LEAF EXTRACT FOLLOWING CEREBRAL ISCHEMIA/REPERFUSION INJURY - Ilesanmi, Omotayo B.; Akinmoladun, Afolabi C.; Olayeriju, Olanrewaju Sam; Saliu, Ibrahim Olabayode; Olaleye, M. Tolulope; Akindahunsi, Afolabi A. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Oxidative stress plays a significant role in stroke pathogenesis. Hence, plants rich in antioxidantphytochemicals have been suggested as effective remedies for prevention and treatment of stroke and other neurologicaldiseases. Antiaris africana Engl. (Moraceae) is traditionally used for the management of brain-related problems but there ispaucity of data on its anti-stroke potential.Materials and Methods: Ischemia/reperfusion injury was induced by a 30 min bilateral common carotid artery occlusion/2 h reperfusion (BCCAO/R) in the brain of male Wistar rats. A sham-operated group which was not subjected toBCCAO/R and a group subjected to BCCAO/R without treatment with MEA served as controls. The ameliorative effect of14 days of pretreatment with 50 mg/kg or 100 mg/kg A. africana methanol leaf extract (MEA) on BCCAO/R-mediatedalterations to key markers of oxidative stress (malondialdehyde, reduced glutathione, xanthine oxidase, superoxidedismutase, catalase and glutathione peroxidase) and neurochemical disturbances and excitotoxicity (myeloperoxidase,glutamine synthetase, Na+/K+ ATPase, acetylcholinesterase and tyrosine hydroxylase), was evaluated and compared withthe effect produced by treatment with 20 mg/kg quercetin as a reference standard.Results: Results show that pretreatment with MEA significantly mitigated or reversed BCCAO/R-induced changes in thelevel or activity of the evaluated biochemical markers of oxidative stress, neurochemical dysfunction and excitotoxicitycompared with the BCCAO/R untreated control group (p < 0.05). The effect produced by 100 mg/kg MEA was similar tothat of the reference standard, quercetin.Conclusion: These results revealed the neuroprotective potential of A. africana in stroke and other ischemia-relatedpathologies.Key words: brain ischemia;